REVOLUSI PARADIGMA PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DI INDONESIA - MH, Sutoyo (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: The occurrence of manyenvironmental casesinIndonesia, can not be seenfromthe technicalaspectsorjuridicalper se,but itis necessary to studyaspects of theunderlying. The occurrence ofmanyenvironmental cases, both national and local, mostlysourced fromhuman behaviorirresponsible,do notcare about the environmentandselfish. It is strongly associatedwith theworldview(paradigm)stakeholders, whichon averageis afollowerAnthropocentrismparadigmthat putstheenvironmentsimplyas a meansto meet human needs(shallowecologicalmovement).theAnthropocentrismparadigmmust berevolutionized, ashas beenproven to havedamaged powerenvironment is veryhigh.Religiousparadigmaccording to religious teachingsembraced byeverycitizen,is expected tobe asolution to thesharedenvironmental problemshappened. Withthereligiousparadigmofprotection effortsandenvironmental managementis an obligation thatmust be carried outbasedonthe beliefoncommandments of the Lord.Key word: revolution, anthropocentrism paradigm, religious paradigm.